Creating Civically Motivated Science Students: Why is it Important to Teach Civics in Science Education? (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
Only three of the State of Ohio American Government standards address the teaching of civic responsibility, suggesting that these standards somewhat overlook this very important aspect of education. However, both research in the field and the current state of global affairs suggest that we should be teaching students not only more ways in which they can be successfully civically engaged, but also that we should be teaching civic engagement in our science classrooms. This article identifies the relationship between civic activism and science education while addressing the contemporary world issues that intensify the need to merge both this sect of social studies and scientific disciplines.